Serum Level of Immunosuppressants as a Marker of Effectiveness of Pharmaceutical Education in Solid Organs Transplantation - Luz, Thayse Ventura; Alves, Paola Hoff; Muneretto, Camila Silva (Brazilian Journal of Transplantation, 2024)
Solid organ transplantation promotes an increase in the quality of life of those with diseases that compromise the functioning of a specific organ, maximizing graft survival and reducing the need for retransplantation is essential. Post-transplant medication adherence is one of the factors that influence positive clinical outcomes, with this, the importance of pharmacotherapeutic follow-up at the hospital and outpatient level with the clinical pharmacist is addressed. Objectives: To verify the impact of pharmacotherapeutic guidance and follow-up on the compliance of serum levels of calcineurin inhibitors in lung and liver transplant patients. Methods: Descriptive and retrospective study with adult liver and lung transplant patients using calcineurin inhibitors, aged over 18 years, between 2018 and 2020. The variation index was calculated through the mean and standard deviation of serum levels collected during the index hospitalization, being used to assess the adequacy of serum levels in three different periods. Results: A total of 84 patients were transplanted, including 64 patients (45 liver transplants and 19 lung transplants). In a subgroup analysis, 42.22% of the liver patients and 47.37% of the lung transplant recipients did not have the same serum level in the first post-discharge consultation. After 1 year of transplantation and differentiated outpatient follow-ups, the target serum levels were reached in 63.16% and 77.78% of the studied populations, respectively. Conclusion: The importance of clinical action was demonstrated from the reflection obtained on the adequacy and conformity of serum levels of calcineurin inhibitors, not only at the hospital level but mainly on the pharmacotherapeutic follow-up carried out on an outpatient basis, in which we observed a more expressive value.